Fluktuasi Nilai HbA2 pada Carrier β-Thalasemia: Literature Review - Qoriba, Fathan; Sangging, Putu Ristyaning Ayu; Maulana, Muhammad; Lisiswanti, Rika (Medula, 2024)
Thalassemia is a form of microcytic anemia caused by impaired synthesis of the globin protein in hemoglobin, with β-thalassemia being one of the most common types. β-thalassemia arises from mutations in the β-globin gene located on chromosome 11, resulting in reduced or absent production of the β-globin chain. According to the World Health Organization (WHO, 2019), the global prevalence of β-thalassemia major is estimated at 39.96 million people (5.2% of the world’s population), with 1.5% identified as carriers. In Indonesia, the 2018 Riskesdas survey reported 7,209 cases of β-thalassemia. The decreased synthesis of the β-globin chain leads to elevated levels of HbA2 and HbF. β-thalassemia is classified into three categories: minor, intermediate, and major. This review focuses on the characteristics of HbA2 and its significance in diagnosing the β-thalassemia carrier. This article is a narrative literature review that examines various studies on HbA2 (HbA2) and its role in the β-thalassemia carrier. The literature reviewed was sourced from several databases, including PubMed, Google Scholar, and Elsevier, using the keywords "Carrier β-thalassemia" and "HbA2." The selected studies span from 2010 to 2024. Hemoglobin A (HbA) is the primary type of hemoglobin found in adults, with HbA2 and HbF serving as minor components. Individuals with β-thalassemia exhibit reduced or absent production of the β-globin chain, leading to an imbalance between α and β chains and an associated increase in HbA2 levels. Elevated HbA2 levels are commonly observed in β-thalassemia carriers, making this measurement important for predicting the risk of β-thalassemia major in their offspring. Studies suggest that HbA2 levels can be influenced by conditions such as megaloblastic anemia and iron deficiency. Additionally, factors like pregnancy and serum ferritin levels have been investigated, with mixed findings on their potential impact on HbA2 levels.